PERAN MUSIK TUDDUKAT DALAM RITUAL ARAT SABULUNGAN DI KABUPATEN MENTAWAI - Tatubeket, Ruth Meliani; Agustina, Agustina; Efi, Agusti (Jurnal Sosiologi Agama, 2019)
Tuddukat is traditional music of Mentawai people., consist of three drums from wood, Ina (the bigger Tuddukat ), Sileleite (midle of tuddukat), and Toga (Small tuddukat). Tuddukat used by mentawai people for expressing their feeling, such us sad, happy, sorrow, in differance occassion. In used, tuddukat is a medium of communication among people and their own Gods (Taeka). In other hand, tuddukat performed in special occasion, deal with the desires of mentawai people will communicating with other or Taeka, it presenting by Sikerei (a person as medium to talk to Gods). Finaly, Tuddukat is media communitation among two dimensi, seen and unseen worlds Keywords: Tuddukat, seen and unseen worlds, Taeka